O caminho dos santos à luz das hagiografias cristãs árabes: as relações entre cristãos e muçulmanos no Dār al-Islām. Séc. VIII e IX E.C. (Ágora Journal, 2021)
Tensions between religious communities, Christian and Islamic, have been placed since political domination. These Christian communities, in their multiple perspectives and theological perspectives, produced a diversity of texts, and in the period proposed, these hagiographic texts were elaborated in Latin, Greek, Syriac and Arabic, presenting the questions of sanctity linked to the debate between the foundations of faith Christian and Muslim, as well as the various apologies or catechetical texts. In this article, we will try to point out some elements of the hagiographies and of this debate in three texts distant, geographically, but belonging to a same period: ends of century VIII and middle of century IX, in which the Muslim political power settled and allowed the proselitismo: the texts, written in Arabic, linked to the context of the chalcedonian communities of Lavras de Mar Sabas and Santa Catarina of Mount Sinai, the Passions of St. Anthony Rawh and Saint 'Abd al-Masīḥ al-Ghassanī.
Keywords: Hagiographies, Arabic’s Christianity, Sainthood, Martyridom.